Research joint ventures: The role of financial constraints - Philipp Brunner; Igor Letina; Armin Schmutzler (University of Bern, Department of Economics, 2022)
This paper provides a novel theory of research joint ventures for financially constrained firms. When firms choose R&D portfolios, an RJV can help to coordinate research efforts, reducing investments in duplicate projects. This can free up resources, increase the variety of pursued projects and thereby increase the probability of discovering the innovation. RJVs improve innovation outcomes when market competition is weak and external financing conditions are bad. An RJV may increase the innovation probability and nevertheless lower total R&D costs. RJVs that increase innovation tend to be profitable, but innovation-reducing RJVs also exist. Finally, we compare RJVs to innovation-enhancing mergers.
Keywords: L13; L24; O31; 330; Innovation; Research Joint Ventures; Financial Constraints; Mergers; Intensity of Competition; Licensing